(untitled) (Vietnam Journal of Community Medicine, 2022)
Objective: To describe the change of practice using food of people at six communes along the Red River in Thai Binh province after integrated communication interventions to reduce the risk of arsenic exposure. Methods: A community intervention study on 1184 people aged ≥ 18 years. Results: The percentage of people who are aware of the signs of arsenic poisoning is low. The proportion of people with correct knowledge and practice about the influencing factors of Arsenic pollution on health after the intervention was higher than before the intervention in both the intervention and control groups, however after the intervention group higher than the control group with p<0.05. The effectiveness of people’s knowledge reached over 70% about the whereabouts of Arsenic in soil, and inorganic fertilizers containing Arsenic. The practice of people using plant protection chemicals according to the instructions achieved 79.4% efficiency. Reducing the use of arsenic-contaminated vegetables and fruits beyond the threshold of over 70% effectiveness. Conclusions and recommendations: There is a change in people’s food use practice before and after the intervention, so it is necessary to maintain active forms of communication in local activities and expand the measure. Active communication interventions for communes at risk of arsenic contamination to limit the risk of arsenic exposure to food to improve people’s quality of life.